2019
DOI: 10.1002/tal.1663
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of lateral load behavior of H‐shaped precast reinforced concrete shear walls with bolted steel connections

Jian Sun,
Hongxing Qiu,
Yong Lu
et al.

Abstract: Summary This paper presents an experimental study of H‐shaped precast reinforced concrete shear walls involving vertical connections under combined vertical and lateral loading. The H‐wall is composed of two prefabricated flange wall panels: one prefabricated web wall panel and vertical bolted steel connections between the flange and web panels. The assembling of the H‐wall is completely dry without any in situ casting. Three H‐wall specimens were constructed and tested to investigate the mechanical behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…For example, different types of shear walls have been studied, including linear type, I-shaped, L-typed, and T-shaped. Several studies focused on the influence on the seismic behavior of these shear walls exerted by the following factors: the length of the splicing zone, the length of the ribs, the material of the splicing zone, and the form of the splicing zone(Sun et al [11], Song et al [12], LU et al [13], JGJ101-96 [14], Smith et al [15], Pekau et al [16], Soudki et al [17], LI et al [18], Soudki et al [19]). Nevertheless, there are few studies on the prefabricated frame-shear structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, different types of shear walls have been studied, including linear type, I-shaped, L-typed, and T-shaped. Several studies focused on the influence on the seismic behavior of these shear walls exerted by the following factors: the length of the splicing zone, the length of the ribs, the material of the splicing zone, and the form of the splicing zone(Sun et al [11], Song et al [12], LU et al [13], JGJ101-96 [14], Smith et al [15], Pekau et al [16], Soudki et al [17], LI et al [18], Soudki et al [19]). Nevertheless, there are few studies on the prefabricated frame-shear structure.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the partially prefabricated reinforced concrete shear wall performs well. Sun Jian et al 9,10 conducted a low cyclic loading test on the prefabricated reinforced concrete shear wall by using connection steel frames and high‐strength bolts. Their results showed that this fabricated shear wall is of high bearing capacity and good ductility and energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a significant amount of research has been conducted worldwide on the design and seismic behavior of precast concrete frame structures and precast concrete shear wall structures. The research on precast concrete shear wall structures was mostly focused on the connections of different types, that is, emulative, posttensioned, hybrid, and in posttensioned walls endowed with energy dissipation …”
Section: Introductionmentioning
confidence: 99%
“…Henin and Morcous investigated the use of nonproprietary bar splice sleeves for precast concrete construction, and the test results indicated that the proposed bar splice sleeves exhibit adequate capacity to fully develop reinforcing bars while being simpler to use and more economical than current proprietary splice sleeves. An assembly method was then proposed for precast reinforced concrete shear walls using dry connection through a horizontal steel connector (H‐connector) and high‐strength bolts . In addition, one design‐oriented analytical model to estimate the nonlinear lateral load behavior of unbonded posttensioned walls was introduced and validated with available experimental results .…”
Section: Introductionmentioning
confidence: 99%